2005
DOI: 10.1103/physrevlett.94.184504
|View full text |Cite
|
Sign up to set email alerts
|

Faraday Instability in a Surface-Frozen Liquid

Abstract: Faraday surface instability measurements of the critical acceleration, ac, and wavenumber, kc, for standing surface waves on a tetracosanol (C24H50) melt exhibit abrupt changes at Ts = 54 • C, ∼4 • C above the bulk freezing temperature. The measured variations of ac and kc vs. temperature and driving frequency are accounted for quantitatively by a hydrodynamic model, revealing a change from a free-slip surface flow, generic for a free liquid surface (T > Ts), to a surface-pinned, no-slip flow, characteristic o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…Only recently have vertically vibrated complex fluids been the subject of experimental [10][11][12][13][14] and theoretical research [15,16]. It was shown that the coupling between the microstructure of complex fluids and the Faraday instability either only slightly modifies the instability (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently have vertically vibrated complex fluids been the subject of experimental [10][11][12][13][14] and theoretical research [15,16]. It was shown that the coupling between the microstructure of complex fluids and the Faraday instability either only slightly modifies the instability (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…by affecting the critical acceleration [10,11] or by delaying the transition to disordered states [14]) or presents non-intuitive behaviours such as stabilized "persistent holes" in shear-thickening fluids [12]. With the notable exception of concentrated colloidal and granular suspensions [12,17], most of these works were performed on fluids whose viscoelasticity is only a small perturbation [10,13,14] to Newtonian behaviour. The case of a complex fluid with significant viscoelasticity was addressed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that the inextensible behavior of the free surface when Ma . 1 has been exploited by Huber et al 22 to analyze the formation of Faraday waves on the free surface of normal alkane under surface freezing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…We note from Figure 5 that (a c , k c ) display the same discontinuous behavior as the viscous and elastic parameters do across the thermal phase transition temperature. However, a different mechanism for discontinuity of these critical parameters was measured experimentally by Huber et al [57] during the surface freezing of a polymer monolayer made of tretraconazole melt. They found that a decrease of temperature leads to the formation of a monolayer at the interface of polymer-air that changed the surface tension but without an observable quantitative change of bulk viscosity.…”
Section: Thermal Phase Transition Effect On Surface Dynamicsmentioning
confidence: 93%
“…A comprehensive experimental determination of the bulk Leslie viscosities of the most known liquid crystals in an ample interval of temperatures near their critical phase transition is scarce [53]. Their values can lead to the prediction of enhanced macroscopic hydrodynamic response on the parametric surface dynamics of liquid crystals [39,40], or polymer melts [57]. A similar experimental program may be set up for studying lyotropic liquid crystals to determine the viscosities and elastic parameters as a function of temperature.…”
Section: Thermotropic Nematic Liquid Crystal Layersmentioning
confidence: 99%